Digitalisasi Alat Ukur Ph Air Pada Budi Daya Ikan Air Tawar - Gumelar, Tommy; Bakti, Indra (Jurnal Teknologi Informasi (JUTECH), 2021)
The high market demand for freshwater fish needs, because it has become a daily commodity for Indonesian people from upper economic circles or low incomes, the need for freshwater fish is very high. The delicious taste of meat and the vitamins contained in freshwater fish are very good for the human body, therefore aquatic fish cultivators are developing to meet market needs. Various efforts were made to meet the market demand for freshwater fish, starting from increasing the number of ponds, improving fish feed to meet protein needs and paying attention to the pH of freshwater ponds. The use of digitalization of freshwater pH measurements is applied to facilitate control of the tolerance level of freshwater fish.